2021
DOI: 10.1002/aet2.10714
|View full text |Cite
|
Sign up to set email alerts
|

Staff perceptions of the implementation of a trauma video review program at a level I trauma center

Abstract: Objectives: Successful implementation of any new technology requires extensive engagement with front-line staff. We explored the perceptions of emergency department and trauma staff about a trauma video review program (TVR) prior to implementation of the first such program in Canada at our level I trauma center. Methods:We conducted semi-structured individual interviews and in situ small group interviews with 35 multidisciplinary ED and trauma staff members of a teaching and research hospital in Toronto, Canad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The use of cameras in TRs is highly uncommon despite the benefits they could provide and staff’s positive attitude towards them (Dainty et al , 2021). It is known that the legal ramifications are one of the main barriers to video surveillance in TRs (Dumas et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The use of cameras in TRs is highly uncommon despite the benefits they could provide and staff’s positive attitude towards them (Dainty et al , 2021). It is known that the legal ramifications are one of the main barriers to video surveillance in TRs (Dumas et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the need for strong team dynamics, leadership, and quick and efficient demonstration of protocols and procedures make video review feedback incredibly effective (Davis et al, 2013; Wurster et al, 2017). Prior studies have also demonstrated that providers often feel anxiety surrounding the possibility of video review (Dainty et al, 2021; Davis et al, 2013). Our study is consistent with prior literature demonstrating the educational value of TVR; however, it expands upon concerns that providers may associate these educational sessions with anxiety and possibly even punitive intent.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits, there is a concern that this type of program may generate apprehension among participants (Dainty et al, 2021). Individual criticism can be seen as punitive in a group setting, and the anxiety surrounding TVR can present a barrier to implementation.…”
mentioning
confidence: 99%
See 1 more Smart Citation